Neural Basis of Enhanced Executive Function in Older Video Game Players: An fMRI Study - Wang, Ping; Zhu, Xing-Ting; Qi, Zhigang; Huang, Silin; Li, Hui-Jie (Frontiers in Aging Neuroscience, 2017)
Video games have been found to have positive influences on executive function in older adults; however, the underlying neural basis of the benefits from video games has been unclear. Adopting a task-based functional magnetic resonance imaging study targeted at the flanker task, the present study aims to explore the neural basis of the improved executive function in older adults with video game experiences. Twenty video game players (VGPs) and twenty non-video game players (NVGPs) of 60 years of age or older participated in the present study, and there are no significant differences in age (t = 0.62, p = 0.536), gender ratio (t = 1.29, p = 0.206) and years of education (t = 1.92, p = 0.062) between VGPs and NVGPs. The results show that older VGPs present significantly better behavioural performance than NVGPs. Older VGPs activate greater than NVGPs in brain regions, mainly in frontal-parietal areas, including the right middle frontal gyrus, the right inferior frontal gyrus, the left supramarginal gyrus, the right angular gyrus, the right precuneus and the left paracentral lobule. The present study reveals that video game experiences may have positive influences on older adults in behavioural performance and the underlying brain activation. These results imply the potential role that video games can play as an effective tool to improve cognitive ability in older adults.